Utilização de técnicas espectrofluorimétricas e quimiométricas na análise de biodiesel e de suas misturas com óleo diesel - Camila Nunes Costa Corgozinho (2009)
In order to increase the percentage of biofuels in the national energy source, biodiesel has been compulsory added to diesel oil since January 2008, current content being 3 % (v/v). However, in spite of fiscalization and monitoring actions, samples of B3 with quality parameters out of specification have been marketed. Among the nonconformities, the most common are out of specification biodiesel content and alteration of physiochemical parameters, which might be caused by several factors, such as adulteration. The method used to quantify biodiesel in diesel mixtures is not appropriate to confirm that the mixture actually contains biodiesel, and the assays carried out are not enough to detect adulterations. In view of this, the objective of this work was to develop a low cost and simple analytical method for biodiesel quantification in mixtures with diesel oil and the detection of adulterations, combining multivariate calibration and spectrofluorimetry. The proposed method enabled the separation of pure diesel oil samples from their mixtures with biodiesel and even from samples adulterated with kerosene, vegetable oil, or residual oil. The quantification of biodiesel in diesel oil mixtures ranging from 0.40 to 19.00 % (v/v) was carried out with forecasting errors under 0.6 % (v/v). In the 4.50 to 20.00 % (v/v) range, the relative mean error was below 4 %. For the quantification of adulterations, the relative mean errors were equal to 3 % for mixtures with kerosene, 4 % with residual oil and 6 % for vegetable oil. The method is simple, fast, does not require pretreatment of the samples and may be carried out in loco, presenting low cost and accuracy.